Herb Gintis on economics and welfare, political economy, and evolution and human behavior - Putterman, Louis (Frontiers in Behavioral Economics, 2025)
Herbert Gintis's research cut to the heart of what scientists must probe in order to understand what kinds of economic arrangements are possible, and which of those arrangements have the potential to make possible human flourishing among the largest numbers of people. Early in his career, he recognized that economics' standard depiction of human actors constituted a barrier to serious research on these questions. Gintis can be called a behavioral economist, but he was also an adept practitioner of neoclassical-style modeling, a game theorist, an insatiable reader of psychology, anthropology and sociology, a contributor to gene-culture co-evolutionary analysis, and a sociobiologist in the broad sense of appreciating that the evolved Homo sapiens rewards inspection with the eye of an ethologist.JEL codes: I31, C70, D63, B59, A12.